2016
DOI: 10.18632/oncotarget.13000
|View full text |Cite
|
Sign up to set email alerts
|

Is chronic hepatitis B infection a protective factor for the progression of advanced pancreatic ductal adenocarcinoma? An analysis from a large multicenter cohort study

Abstract: PurposeWhether the progression of advanced pancreatic ductal adenocarcinoma (PDAC) patients could be affected by HBV exposure remains to be determined. Therefore, we conducted this study to assess the effect of HBV infection on PDAC progression among a large cohort in China.MethodsA multicenter cohort study was conducted to explore whether liver metastasis and overall survival in locally advanced and metastatic PDAC could be affected by HBV infection. In this study, we collected 1,526 advanced PDAC patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It has been reported that HBV infection status is closely associated with liver metastases of malignancies. In a previous study, Chen et al examined four types of HBV infection status and found that chronic HBV infection decreased the risk of liver metastases in patients with advanced pancreatic ductal adenocarcinoma ( 13 ). Qiu et al described that the occurrence of liver metastasis of colorectal cancer was significantly lower in the chronic HBV infection group (HR: 0.29, 95% CI: 0.12–0.72, P<0.01), inactive carrier group (HR: 0.36, 95% CI: 0.22–0.59, P<0.01) and resolved HBV infection group (HR: 0.63, 95% CI: 0.46–0.85, P<0.01) than in the non-infection group ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HBV infection status is closely associated with liver metastases of malignancies. In a previous study, Chen et al examined four types of HBV infection status and found that chronic HBV infection decreased the risk of liver metastases in patients with advanced pancreatic ductal adenocarcinoma ( 13 ). Qiu et al described that the occurrence of liver metastasis of colorectal cancer was significantly lower in the chronic HBV infection group (HR: 0.29, 95% CI: 0.12–0.72, P<0.01), inactive carrier group (HR: 0.36, 95% CI: 0.22–0.59, P<0.01) and resolved HBV infection group (HR: 0.63, 95% CI: 0.46–0.85, P<0.01) than in the non-infection group ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in China, chronic active infection with HBV was associated with statistically significant decreased rates of synchronous and metachronous metastases in patients with advanced PDAC and improved survivals for patients with stage IV PDAC, compared with patients with no HBV infection (70,71). No differences were observed for inactive carriers (70). This observation is reminiscent of the fact that lower rates of liver metastases of colorectal cancer origin in patients with chronic liver diseases were previously highlighted in a meta-analysis (66).…”
Section: Is There Any Influence Of Hbv Infection On Clinico-pathologimentioning
confidence: 99%